Antioxidant and Antibacterial Activity of Endophytic Fungi Isolated from Fruit of Sungkai (Peronema canescens) - Oktiansyah, Rian; Widjajanti, Hary; Setiawan, Arum; Elfita (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Peronema canescens, often known as sungkai, is widely used and can be found all around Indonesia. The public believes that the leaves may reduce fever and strengthen the immune system. However, the effectiveness of sungkai fruit has not been thoroughly investigated. In this research, we looked at endophytic fungus extracts from sungkai fruit’s that have antioxidant and antibacterial properties. The study’s results will serve as the foundation for further investigation into the development of potential natural chemicals with antioxidant and antibacterial properties. Morphologically, the endophytic fungi isolated from sungkai fruit were identified. The antioxidant and antibacterial properties of endophytic fungal extracts were studied using the DPPH technique and the paper disk diffusion method. By employing molecular identification and column chromatography to separate the active compounds, the most likely endophytic fungal isolates were found based on the results of the bioactivity tests. Using 1D NMR spectroscopic methods, the chemical’s structure was determined, and the results were compared to NMR data for the same compound published in the literature. Fruit of sungkai had 8 strains of endophytic fungus (RBH1-RBH8). Strong antibacterial and very strong antioxidant activity were shown by the RBH5 isolate (IC50 < 20 μg/mL). Pythium periplocum was determined to be the RBH5 isolate based on molecular testing. Pure chemical compound extracted from RBH5 isolates shown highly potent and potent antibacterial and antioxidant effects. The chemical compound was identified by spectroscopy as 3-hydroxy-4(hydroxy(4-hydroxyphenyl)methyl)-γ-butyrolactone. The results of this study serve as the foundation for developing compounds as pharmaceutical raw materials via further research phases.